Higher Medicare Expenditures Are Associated With Better Integrated Care as Perceived by Patients. Issue 7 (13th July 2021) - Kerrissey, Michaela J.; Frean, Molly; Traboulsi, Abd Al-Rahman; Singer, Sara J.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Integrated care that is continuous, coordinated and patient-centered is vital for Medicare beneficiaries, but its relationship to health care expenditures remains unclear. Research Objective: This study explores—for the first time—the relationship between integrated care, as measured from the patient's perspective, and health care expenditures. Methods: Subjects include a sample of continuously eligible fee-for-service Medicare beneficiaries (n=8807) in 2015. Analyses draw on 7 previously validated measures of patient-perceived integrated care from the 2015 Medicare Current Beneficiary Survey. These data are combined with 2015 administrative utilization data that measure health care expenditures. Relationships between patient-perceived integrated care and costs are assessed using generalized linear models with comprehensive control measures. Results: Patients who perceive more integrated care have higher expenditures for many, but not all, cost categories examined. Aspects of integrated care pertaining to primary provider and specialist care are associated with higher costs in several areas (particularly inpatient costs associated with specialist knowledge of the patient). Office staff members' knowledge of the patient's medical history is associated with lower home health costs. Conclusions: Patients who experience their care as more integrated may have higher expenditures on average. Thoughtful policy choices, further research, and innovations that enable patients to perceive integrated care at lower or neutral cost are needed.